Formation of corporate identity in the company branding system - Cheng Xiaohua (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the process of forming a corporate style as a component of a company's branding system. The subject of research includes theoretical and methodological principles, as well as practical aspects, related to improving the formation of the corporate style of banking institutions in modern conditions. The purpose of the master's thesis is to substantiate theoretical approaches and develop practical provisions for the formation of a corporate style within the company's branding system. This aims to enhance recognition, competitive advantages, and the establishment of a unique market identity. Tasks of a qualifying master's thesis include: • to investigate the historical foundations of corporate style formation; • to reveal the essence of identity as the foundation of a company's brand identity; • to study the methodology for developing a corporate style for companies; • to provide the technical and economic characteristics of JSC CB "PrivatBank"; • to analyze the corporate style concept of JSC CB "PrivatBank"; • to examine the features of JSC CB "PrivatBank's" advertising products in the context of modern branding; • to propose improvements to the process of forming the brand strategy of JSC CB "PrivatBank"; • to provide recommendations for enhancing the corporate style of JSC CB "PrivatBank"; • to propose directions for developing the communication policy of JSC CB "PrivatBank" as a component of branding. Practical significance: The obtained results are significant in developing specific recommendations aimed at enhancing the corporate style of banks to strengthen their competitiveness. The proposed solutions enable optimization of branding strategies, improvement of client interactions, and assurance of long-term stability in the banking market. This study emphasizes the importance of a well-developed corporate style in creating a strong market identity, increasing competitive advantages, and ensuring the sustainability of banking institutions in a dynamic market environment.
Scientific adviser: Denchyk Iryna, senior lecturer
Keywords: SOCIAL SCIENCES::Business and economics; company's branding system; company; corporate identity; branding; design; competitiveness of the company